Toward a generic framework of perceived negative manager/leader behavior: A comparative study across nations and private sector industries. Issue 4 (15th February 2022) - Patel, Taran; Hamlin, Robert G.; Louis, Dima
Abstract: Reviewing three relevant streams of extant literature reveals a marked absence of a generic framework composed of a full range of negative manager/leader behaviors (from moderate to extreme) across sectors and countries, a void particularly detrimental to the effectiveness of management and leadership development (MLD) programs. To address this concern, we conduct a multiple cross‐case/cross‐nation comparative analysis (MCCA) of data collected from our own 13 previous empirical replication studies (using the critical incident technique) of effective/ineffective managerial/leader behavior across nine culturally diverse countries and varied private sector industries, resulting in a comprehensive framework of perceived negative manager/leader behavior. Our generic framework is composed of five behavioral dimensions: inadequate functional behavior, unethical behavior, impersonal domineering behavior, depriving behavior, and closed/negative‐minded behavior, and lends support to the universal school of culture in business literature by showing that neither national culture nor sectorial specificities influence people's perceptions of negative manager/leader behavior. It also stresses the importance of the mundane (as opposed to the glorious) in managerial/leadership work by revealing that employees' perceptions of negative manager/leader behavior include not only conspicuously "bad" behaviors but also less conspicuous "poor" behaviors.